Liver-allocation policies for patients affected by HCC in Europe - DE CARLIS, LUCIANO GREGORIO; Di Sandro, S; Centonze, L; Lauterio, A; Buscemi, V; De Carlis, R; Ferla, F; Sguinzi, R; OKOLICSANYI, STEFANO; Belli, L; STRAZZABOSCO, MARIO (Current Transplantation Reports, 2016)
The main goal of organ allocation systems is to guarantee an equal access to the limited resource of liver grafts for every patients on the waiting list, balancing between the ethical principles of equity, utility, benefit, need, and fairness. The European heath care scenario is very complex, as it is essentially decentralized and each Nation and Regions inside the nation, operate on a significant degree of autonomy. Furthermore the epidemiology of liver diseases and HCC, which is different among European countries, clearly inpacts on indications and priorities. The aims of this review are to analyze liver allocation policies for hepatocellular carcinoma, among different European. The European area considered for this analysis included 5 macro-areas or countries, which have similar policies for liver sharing and allocation: Centro Nazionale Trapianti (CNT) in Italy; Eurotransplant (Germany, the Netherlands, Belgium, Luxembourg, Austria, Hungary, Slovenia, and Croatia); Organizacion Nacional de Transplantes (ONT) in Spain; Etablissement français des Greffes (EfG) in France; NHS Blood & Transplant (NHSBT) in the United Kingdom and Ireland; Scandiatransplant (Sweden, Norway, Finland, Denmark, and Iceland). Each identified area, as network for organ sharing in Europe, adopts an allocation system based either on a policy center oriented or on a policy patient oriented. Priorization of patients affected by HCC in the waiting list for deceased donors liver transplant worldwide is dominated by 2 main principles: urgency and utility. Despite the absence of a common organs allocation policy over the Eurpean countries, long-term survival patients listed for transplant due to HCC are comparable to the long-term survival reported in the UNOS register. However, as the principles of allocation are being re-discussed and new proposals emerge, and the epidemiology of liver disease changes, an effort toward a common system is highly advisable.